Relationship Between Firms’ Performance and Forced CEO Turnover; Empirical Evidence from US Market - Asia Parveen; Hashim Khan (NUML International Journal of Business & Management)
Firm performance (ROA) is widely used as a primary matric of CEO ability. So far, empirics have highlighted the relationship between ROA and forced CEO turnover. In the current study, we extend the literature by highlighting the forced CEO turnover and performance relationship by introducing aspirational performance metric of the firm. We used historical performance, average of last five years ROA as a proxy of aspirational level. First, we find the acceptable negative relationship between ROA and forced CEO turnover. However, the negative relationship is stronger when CEO performance is above aspirational level. In addition, the negative relationship persisted in the last year. Thus, our findings show that likelihood of forced CEO turnover is lower when CEO performance is above the aspirational level and vice versa. Our findings provide a novelty in the existing literature.  Likewise, the managerial implications are also discussed.